Bayesian integrated population model of Baltic grey seals (Halichoerus grypus grypus) informs on population carrying capacity and the impact of Baltic herring (Clupea harengus membras) on reproduction - Vanko, Milena; Helle, Inari; Kunnasranta, Mervi; Ahola, Markus P.; Bäcklin, Britt-Marie; Carlsson, Anja M.; Cervin, Linnea; Persson, Sara; Vanhatalo, Jarno (Elsevier, 2026)
Baltic grey seal (Halichoerus grypus grypus) is a top predator of the Baltic Sea ecosystem that has just recently recovered from near-extinction induced by historical bounty hunting and pesticides. However, increasing seal population has initiated a conflict between seal conservation and fisheries. We also lack understanding of the ecological constraints of grey seal population in the rapidly chancing Baltic Sea. To address these challenges, we developed a Bayesian integrated population model for the Baltic grey seals. We used our model to estimate their historical population development, demography, and life history parameters, and to assess their future prospects under alternative hunting and prey scenarios. Our results show that the grey seal population has recovered to approximately 57,000 seals in 2025, with an average yearly growth rate of 4.9% in the last two decades. The current carrying capacity of Baltic grey seals was estimated at 120,000 individuals, which is 30% larger than previous estimates from historical hunting statistics. The weight-at-age of Baltic herring (Clupea harengus membras) was found to have a strongly positive effect on grey seal reproduction. Scenario predictions suggest that the Baltic grey seal population can remain viable under the current hunting quota of 3050 individuals. However, with yearly hunting of 3600 individuals, probability of extinction was considerable, and depended on both prey quality and the demographic composition of the hunted seals. With yearly harvest of 4800 seals, the population was predicted to go extinct by 2070 at the latest.
Keywords: Bayesian; integrated population model; Baltic grey seal; carrying capacity; herring dependent birth rate; state–space model